2021
DOI: 10.3389/fimmu.2021.712351
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Complete Response of Primary Massive Hepatocellular Carcinoma to Anti-Programmed Death Ligand-1 Antibody Following Progression on Anti-Programmed Death-1 Antibody

Abstract: Hepatocellular carcinoma (HCC) is an aggressive liver tumor that occurs due to chronic liver disease, and it has a high mortality rate and limited treatment options. Immune checkpoint inhibitors have been successfully introduced and used in cancer therapy, among which inhibitors of programmed death ligand-1 (PD-L1) and its receptor programmed death-1 (PD-1) are commonly administered for HCC as combination therapy, including combined anti-angiogenic and immunotherapy combination therapy. We report a case of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Liu et al reported a case of massive HCC with portal hepatic vein tumor thrombus and ALN metastases. The patient received atezolizumab plus bevacizumab and experienced a CR after three cycles of treatment (20). However, an optimal immunotherapeutic strategy for HCC has not been found.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported a case of massive HCC with portal hepatic vein tumor thrombus and ALN metastases. The patient received atezolizumab plus bevacizumab and experienced a CR after three cycles of treatment (20). However, an optimal immunotherapeutic strategy for HCC has not been found.…”
Section: Discussionmentioning
confidence: 99%